Using gypsum to control hydration kinetics of CSA cements. (30th November 2017) - Winnefeld, Frank; Martin, Lukas H.J.; Müller, Christian J.; Lothenbach, Barbara
Highlights: Gypsum accelerates ye'elimite hydration more efficiently than anhydrite. Low amounts of gypsum enhance anhydrite and ye'elimite dissolution. Combination of anhydrite and gypsum beneficial for strength development. Abstract: The effect of the kind of calcium sulfate on the hydration of CSA cements was investigated. Thermal anhydrite, gypsum and a combination of anhydrite with gypsum were used at a constant molar ratio gypsum/ye'elimite of 0.8. With gypsum, ye'elimite dissolved faster than with anhydrite. When approximately 20 mass-% of anhydrite were replaced by gypsum, ye'elimite dissolution was as fast as in the system with plain gypsum. The dissolution of anhydrite was accelerated as well by the presence of gypsum. Thus the replacement of a part of the anhydrite by gypsum is able to enhance hydration kinetics and both early and late compressive strength.